Analgesic and Antioxidant Activities of 4-Phenyl-1,5-benzodiazepin-2-one and Its Long Carbon Chains Derivatives - Terence Nguema Ongone; Redouane Achour; Mostafa El Ghoul; Latyfa El Ouasif; Meryem El Jemli; Laila Chemlal; Yahia Cherrah; Katim Alaoui; Amina Zellou (Journal of Chemistry)
The aim of this work is to deepen the pharmacological effect of 4-phenyl-1,5-benzodiazepin-2-one derivatives which have a similar structure to nonionic surfactants: 4-phenyl-1,5-benzodiazepin-2-one is the hydrophilic head, and the carbon chain is hydrophobic tail. The antinociceptive activity of 4-phenyl-1,5-benzodiazepin-2-one derivatives was determined using acetic acid-induced writhing and tail immersion tests. In addition, the in vitro antioxidant activities of the tested derivatives were determined by using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method and ferric reducing power assay. A single oral administration of these compounds at the doses of 50 and 100 mg/kg significantly reduced the number of abdominal writhes induced by acetic acid injection. Acute pretreatment with 4-phenyl-1,5-benzodiazepin-2-one derivatives at the dose of 100 mg/kg caused a significant increase in the tail withdrawal latency in the tail immersion test. Additionally, a significant scavenging activity in DPPH and reducing power was observed in testing antioxidant assays. Finally, we carried out a study of the antioxidant activity of these derivatives. The results of this study reveal that these compounds have a low antioxidant activity compared to the BHT. It decreases with the polarity of the molecule. The present study suggests that 4-phenyl-1,5-benzodiazepin-2-one derivatives possess potent antinociceptive and antioxidant effects, which suggest that the tested compounds may be useful in the treatment of pain and oxidation disorders.